Headache in pregnancy-a diagnostic dilemma: an unusual case of advanced glioblastoma multiforme in pregnancy: a case report and review of literature - N., Sunanda; K., Mythreyi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
This was a case report of a twenty year old patient with a obstetric score of G2P1L1 with 28 weeks of gestation presented with persistent intractable headache leading to a diagnostic conundrum. Magnetic resonance imaging of the brain revealed an advanced glioma in the right frontal lobe with a mass effect and a midline shift for which emergency surgical resection was sorted followed by chemoradiation which eventually lead to a satisfactory obstetric and perinatal outcome. Glioblastoma multiforme is a rare diagnosis during pregnancy which carries unique challenges to the mother, foetus and the health care providers. A combined effort from a multidisciplinary team is the key for a successful outcome.